Can telehealth increase physical activity in individuals with Rett syndrome? A multicentre randomized controlled trial. (25th October 2022) - Downs, Jenny; Blackmore, A. Marie; Wong, Kingsley; Buckley, Nicholas; Lotan, Meir; Elefant, Cochavit; Leonard, Helen; Stahlhut, Michelle
Abstract: Aim: To evaluate the effects of a physical activity programme on sedentary behaviour and physical activity in ambulant individuals with Rett syndrome (RTT). Method: In this multicentre randomized waitlist‐controlled trial, we recruited 43 ambulatory individuals with RTT in Australia and Denmark. Adequate baseline data were obtained from 38 participants (mean age 20 years, range 6–41, SD 10 years 6 months, one male). All completed the trial. Participants received 12 weeks of usual care ( n = 19) or a goal‐based, telehealth‐supported programme in which activities occurred in their familiar environments ( n = 19). Sedentary time and daily steps were assessed at baseline, post‐test, and 12‐week follow‐up. The data analyst was blinded to group allocation. Results: Sedentary time decreased in the intervention group by 2.7% (95% confidence interval [CI] −6.0 to 0.6) and increased in the control group by 1.3% (95% CI −4.8 to 7.4). Intervention and control groups increased the number of their steps per day by 264.7 (95% CI −72.2 to 601.5) and 104.8 (95% CI −178.1 to 387.7) respectively. No significant differences were found on any outcomes at post‐test. There were three minor adverse events. Interpretation: A goal‐based telehealth intervention seemed to produce small improvements in physical activity for individuals with RTT. Families require more support to increase these individuals' extremely low physical activity levels. What this paper adds: A telehealth‐supported intervention may produce small changes in physical activity in Rett syndrome (RTT). Increasing physical activity in individuals with RTT is challenging for caregivers. Families require substantial out‐of‐home support to increase their children's activity levels. What this paper adds: A telehealth‐supported intervention may produce small changes in physical activity in Rett syndrome (RTT). Increasing physical activity in individuals with RTT is challenging for caregivers. Families require substantial out‐of‐home support to increase their children's activity levels. This multicentre randomized controlled trial tested the effectiveness of an individualized, goal‐based, telehealth‐supported intervention designed to increase physical activity in children and adults with Rett syndrome. Participants were extremely sedentary and gains were small. The study highlights the need for substantial external support for caregivers to increase physical activity in individuals with Rett syndrome. This original article is commented on by Banerjee on pages 446–447 of this issue.